Competencias de innovación en entornos virtuales de aprendizaje basados en gestión del conocimiento (Estudios) - Ampuero Velásquez, Francisco Xavier (2020)
This article shows the status of knowledge management theories, including the typology of organizational learning and personal styles. These theories, especially those related to the different styles of personal learning should be considered in the creation of E-Learning programs in Virtual Learning Environments (VLE). In this way, such programs can tend to the development of innovation competencies in participants. The objective of the article was to define scenarios for each learning style, which serve as a guide for individuals who educate and lead work teams. Qualitative research was conducted based on secondary sources and literature review. Among the main findings, it is highlighted the importance of having study or work teams that have, if possible, individuals with all or most of the personal learning styles, and that they can go through the different stages of the innovation process without staying in the abstract academic isolation where we remain only in ideas and concepts, or the other extreme, with very simple practical applications that are made without prior reflection.